Strategies and techniques for teaching english to deaf children at Antonio Jose De Sucre Elementary School who attend the regular education system in 2011 - Paredes, Rosaura; Zapata, Edita; De Gracia, Edward (David, Panamá : UDELAS, 2011)
This thesis has as fundamental goal, it is to achieve some methodological strategies and techniques for teaching to deaf children, and it will identifiy hoy they can learn english through different activiities with visual material, realia, and other resources. On other hand, it provides to the teachers a guide to facilitate english languaje learning in the classroom withdeaf children. In conclusion, this tool
GENERAL INDEX Dedication Dedication Acknowledgement Acknowledgement General index Chart index Graphic index Introduction CHAPTER I: INVESTIGATION OF THE PROBLEM CHAPTER 2: THEORETICAL FRAMEWORK 2.1. Theoretical framework 2.1.1. Special learning characteristics of deaf children 2.1.2. Concept of deafness 2.1.3. Behavioral characteristics of hearin impaired individuals 2.1.4. Difficulties of deaf children 2.1.5. Cofnitive characteristics 2.1.6. Physical characteristics 2.2. Methodological techniques and strategies for deaf students 2.2.1. Concept 2.2.2. Strategies for teaching english to deaf students 2.2.3. Fostering a positive mainstream experience 2.3. Strategies for presenting information throught written text 2.4. Techniques for teaching english to deaf students 2.4.1. Special adaptation of activities about deaf children for english teachers 2.5. Resources for teaching english to deaf children with its suggestions 2.5.1. Visual aids 2.5.2. Suggestions for designing writen resources 2.5.3. Videotapes 2.5.4. Integration of an intepreter 2.6. Effective use of the white board and visual - aids 2.6.1. Using the white board 2.7. Captioned film video and laser disk And otherS CHAPTER 3: DATA COLLECTION AND ANALYSIS CHAPTER 5: PROPOSAL
Incluye General index
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA -- TEACHING; FACULTY OF SOCIAL AND SPECIAL SCIENCE; ENGLISH DEPARTMENT; LICENCIATURA EN INGLES; ANTONIO JOSÉ DE SUCRE- ELEMENTARY SCHOOL - CHIRIQUÍ; STRATEGIES AND TECHNIQUES